Effects of the Trophobiont Herbivore Calloconophora pugionata (Hemiptera) on Ant Fauna Associated with Myrcia obovata (Myrtaceae) in a Montane Tropical Forest - Roberth Fagundes; Kleber Del-Claro; Sérvio Pontes Ribeiro (Psyche: A Journal of Entomology)
Many studies have investigated the mechanisms behind the structure of arboreal ant assemblages. In this study, the objective was to evaluate the effect of availability of honeydew-producing colonies of Calloconophora pugionata (Membracidae) on the structure of ant assemblages associated with the host plant Myrcia obovata (Myrtaceae) in an Atlantic forest of Minas Gerais (Brazil). Our experiment consisted in a gradual exclusion of hemipteran colonies out of the host plant crown and further record of the ant assemblage response (species richness, composition, and occurrence) to the presence and density of treehopper colonies. The hypothesis was that an increase in the number of trophobiont herbivores results in an increase in tending ant occurrence but a reduction in ant species diversity. Results corroborated our main hypothesis: membracids had a positive effect on the occurrence of ants but negative on species richness. Overall insect occurrence was also reduced with increasing in C. pugionata colonies, probably due to strengthening dominant ant species territory sizes and intensification of patrolling.